2020
DOI: 10.32332/pedagogy.v7i2.1669
|View full text |Cite
|
Sign up to set email alerts
|

English Needs of Occupational Safety and Health (OSH): The Multinational and National Companies’ Voice in Indonesia

Abstract: The vast growths of multinational and national companies to world-class companies in Indonesia result in the advanced demand for English mastery in every working sector including Occupational Safety and Health (OSH). This article aims at investigating the needs and actual use of English in a working environment specifically at OSH. This research adopted mix method which use questionnaire and open-ended interview to obtain the data on the needs of English in OSH field matching to the prerequisite test in recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This conclusion is consistent with the findings of Norris-Holt ( 2001), which found that the majority of students chose "communication with foreigners" above all others as their primary reason for studying English. It also concurs with Bin-Hady and Al-Tamimi (2021); Haryati et al (2020), who found that their participants wanted to use the English language to communicate with their colleagues from abroad. Furthermore, this is in line with the findings of (Hatori, 1977, cited in Treephongphan, 2005, which found that among the major factors contributing to the students' loss of interest were their inability to understand the information being presented in class and the English curriculum being taught as a subject and not as a language for communication.…”
Section: Discussionsupporting
confidence: 86%
“…This conclusion is consistent with the findings of Norris-Holt ( 2001), which found that the majority of students chose "communication with foreigners" above all others as their primary reason for studying English. It also concurs with Bin-Hady and Al-Tamimi (2021); Haryati et al (2020), who found that their participants wanted to use the English language to communicate with their colleagues from abroad. Furthermore, this is in line with the findings of (Hatori, 1977, cited in Treephongphan, 2005, which found that among the major factors contributing to the students' loss of interest were their inability to understand the information being presented in class and the English curriculum being taught as a subject and not as a language for communication.…”
Section: Discussionsupporting
confidence: 86%
“…Looking at the relevant studies from other non-English speaking countries, English language knowledge has already been recognized as a vital competence in many companies and workers in the OSH context even before the COVID-19 pandemic. For example, the English language skills were identified in playing an essential role in the working environment and with OSH in Indonesia ( 20 ), but these conclusions have been based on other aspects. The study states that sufficient skills of the English language are “more required for communicating to expatriates, leading the meeting, doing the presentation, writing reports and designing Standard Operational Procedure.” A survey in the Philippines has shown that the low language proficiency of employees in the workplace limits their growth potential in the workplace and negatively impacts worker safety ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, additional efforts should be made to raise awareness of employers on the importance and added value to the OSH, and on the general business performance of the company in case the company employs well-educated OSH experts. Therefore, during the recruitment process of OSH experts, attention should be paid if the applicant has solid knowledge and skills of general OSH vocabulary ( 20 ). Secondly, it should be mentioned that one of the simplest and most efficient ways is to invest in the development of a specialized language training program by designing the English for Specific Purposes course for OSH experts ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research applied the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop the course and the materials. There have been several studies in the ESP field which focused on the needs of the students (Aldohon, 2014;Gestanti et al, 2019;Haryati et al 2019, Hariyanto et al 2022, Khalid 2016), but there have not been a number of research using the full ADDIE model. Therefore, this research will give insight for the other teachers to use this ADDIE model in their program.…”
Section: Introductionmentioning
confidence: 99%